2021
DOI: 10.3390/educsci11110675
|View full text |Cite
|
Sign up to set email alerts
|

“We’ve Always Been Engineers:” Indigenous Student Voices on Engineering and Leadership Identities

Abstract: Background: How do Indigenous engineering students describe their engineering leadership development? The field of engineering has made only slow and modest progress at increasing the participation of Indigenous people; an identity-conscious focus on leadership in engineering may help connect the practice of engineering with Indigenous students’ motivations and values. Methods: This study utilized a grounded theory qualitative approach to understand how Indigenous engineering students at a U.S.-based universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Primarily focused on the development of an engineering leadership identity, the authors of this grounded theory study found resonance in the LID model, particularly the transition from seeing leadership as behaviors exercised by those with formal authority to seeing leadership as a community‐oriented process. Moreover, the findings demonstrated how Indigenous college students understood and practiced decolonized leadership , highlighting the importance of the “community uplift that restores the sovereignty of First Nations” (Kwapisz et al., 2021, p. 15).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Primarily focused on the development of an engineering leadership identity, the authors of this grounded theory study found resonance in the LID model, particularly the transition from seeing leadership as behaviors exercised by those with formal authority to seeing leadership as a community‐oriented process. Moreover, the findings demonstrated how Indigenous college students understood and practiced decolonized leadership , highlighting the importance of the “community uplift that restores the sovereignty of First Nations” (Kwapisz et al., 2021, p. 15).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Additionally, Xu (2019) found academic success was a critical factor to building leaders' self-confidence, and that the participants reported that their experiences of leadership development were rapid. Kwapisz et al (2021) also used the LID model to study the leadership development of Indigenous engineering students. Primarily focused on the development of an engineering leadership identity, the authors of this grounded theory study found resonance in the LID model, particularly the transition from seeing leadership as behaviors exercised by those with formal authority to seeing leadership as a communityoriented process.…”
Section: Racial Ethnic and Indigenous Identities And Lidmentioning
confidence: 99%